Magnetic mesoporous material derived from MIL-88B modified by l-alanine as modified QuEChERS adsorbent for the determination of 6 pesticide residues in 4 vegetables by UPLC-MS/MS. (1st August 2022) - Wang, Meng; Wang, Jingjing; Wang, Kangkang; Zhang, Liugen; Cao, Xianglei; Guo, Cheng; Wang, Jide; Wu, Bin
Highlights: Magnetic material with mesoporous structure was successfully synthesized by direct carbonization of MIL-88B modified with l -alanine. Magnetic mesoporous material as QuEChERS adsorbent can effectively remove the interfering substances in vegetables. A rapid QuEChERS sample treatment method for the simultaneous determination of carbamate and neonicotinoid pesticides was established. The recovery was 73.9–107.7%, RSD was ≤ 16.9%, show that the method is reliable. Abstract: More and more attention has been paid to the improved QuEChERS (quick, easy, cheap, effective, rugged and safe) method in dealing complex sample matrices, especially for the study of QuEChERS adsorbents. In this study, a magnetic mesoporous material, which was derived from MIL-88B modified by l -alanine, was synthesized as modified QuEChERS adsorbents for the simultaneous determination of multiple pesticides (Methomyl, Isoprocarb, Carbofuran, 3-Hydroxycarbofuran, Acetamiprid, Imidacloprid) in Chinese cabbage, celery, long bean and leek. The prepared magnetic adsorbents can effectively remove interfering substances from the sample, and the proposed modified QuEChERS method can reduce sample pretreatment time via an external magnetic field. To achieve the best performance of QuEChERS method, the clean-up time and amount of QuEChERS adsorbents were investigated. Under the optimized conditions, a simple, rapid and sensitive method for the determination of 6 pesticide residues in vegetables was established by coupling the modified QuEChERS to ultrahigh-performance liquid chromatography-tandem mass spectrometry. Excellent sensitivity (The limit of detection for the 6 pesticides ranged from 0.001 to 0.020 µg kg −1 ), satisfactory linearity (r 2 ≥ 0.9952), good recovery (73.9–107.7%) and good precision (3.6–16.9% for intraday relative standard deviation, 0.5–15.0% for interday relative standard deviation) were obtained. Compared with traditional QuEChERS method, the proposed method is simple, cost-effective, and efficient, which indicates that the method can be used to detect carbamate and neonicotinoid pesticides in real samples and provide an excellent pretreatment technique for the detection of trace multi-analytes from complex substrates.